The Relationship of Fatty Acid Consumption with Total Cholesterol Level in Coronary Artery Disease Patients - Nurhayani, Elsa; Kusdalinah, Kusdalinah; Kamsiah, Kamsiah (Media Gizi Indonesia, 2024)
Coronary artery disease is one of the significant causes of death and is still a health problem for developed and developing countries. Increased cholesterol in the blood is caused by heredity and high-fat consumption. The effect of dietary fat on artery disease is related to the impact of fatty acid components and cholesterol on blood cholesterol. This study aims to determine the relationship between consumption of Saturated Fatty Acids (SFA), Monounsaturated Fatty Acids (MUFA), and Polyunsaturated Fatty Acids (PUFA) with total cholesterol levels in patients with coronary artery disease. The research design used was descriptive-analytic in clinical nutrition with a cross-sectional approach. The population in this study were 405 patients with coronary artery disease at the artery clinic of RSUD Dr. M. Yunus Bengkulu. The sample was 32 patients collected using a purposive sampling technique. Using the Chi-Square test, data analysis was used to determine the relationship between the consumption of SFA, MUFA, and PUFA with total cholesterol levels in patients with coronary artery disease. The study's results found a significant relationship between SFA consumption and coronary artery disease. Still, conversely, there was no significant relationship between MUFA and PUFA consumption with total cholesterol level in coronary artery disease patients, namely that SFA consumption was inadequate (p-value = 0.043, OR = 0.407), inadequate MUFA consumption (p-value = 0.710), and inadequate of PUFA consumption (p-value= 0.465). Saturated fatty acids are related to total cholesterol in coronary artery disease while conversely to monounsaturated fatty acids and polyunsaturated fatty acids.